The Influence of the Number of Livestock Deaths and Group Support Due to Foot and Mouth Disease on Farmers' Commitment to Continuing Beef Cattle Businesses in Kebumen Regency - Saputri, Ameilia; Muatip, Krismiwati; Cahyo, Danang Nur; Santoso, Fawwaz Alnuari (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
This research aimed to determine the influence of the number of livestock deaths due to Foot and Mouth Disease (FMD) and group support on farmers' commitment to continuing the beef cattle business in Kebumen Regency. Group support consists of emotional support and informative support. Commitment is divided into three, namely affective commitment, normative commitment, and continuous commitment. The research method used is a survey. The location was determined using purposive sampling (intentionally), namely Urut Sewu, Kebumen Regency, which is the center for the development of PO Kebumen beef cattle and has the most cases of FMD in Central Java. Respondents were taken using purposive sampling, totaling 120 farmers whose livestock were affected by FMD according to data from the Kebumen Agriculture and Food Service. Data analysis uses descriptive analysis and logistic regression analysis. The results showed that the number of livestock deaths due to FMD was 12 cattle, emotional support in group support was 50.83% in the medium category, informative support in group support was 50.83% in the medium category, affective commitment was 86.6% in the high category, normative commitment was 85.83% in the high category, and continuous commitment was 86.6% in the high category. The results of the logistic regression analysis show that livestock deaths have a significant effect on farmers' commitment to continuing the beef cattle business in Kebumen Regency. Group support does not have a significant effect on farmers' commitment to continuing the beef cattle business in Kebumen Regency.